2003
DOI: 10.17660/actahortic.2003.619.50
|View full text |Cite
|
Sign up to set email alerts
|

Micropropagation Technology in Early Phases of Commercial Seed Potato Production

Abstract: ^MoS^SO^ Propositions 1. The seed potato industry in the province of Alberta (Canada) will be enhanced by the introduction of microtubers in the seed production system. (this thesis)2. Jasmonates stimulate the production of potato microtubers and their performance in the greenhouse production of minitubers. (this thesis)3. Genotypic responses to in vitro conditions may determine the success or failure of the introduction of the method to a new cultivar.4. GMO potato can be a public enemy or a friend.5. The Dut… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
2
0
4

Year Published

2007
2007
2021
2021

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 70 publications
(95 reference statements)
0
2
0
4
Order By: Relevance
“…This method is very important for plant propagation for example the use of this method in seed production has ensued in mass production of clean potato seeds within a short period of time. In support of this, Pruski (2001) revealed that the method is characterized by its flexibility in terms of the rapid multiplication of seedlings. This method has been adopted in several countries like Vietnam where it revolutionized production of potato seeds.…”
Section: Clean Seed Production Technologiesmentioning
confidence: 77%
“…This method is very important for plant propagation for example the use of this method in seed production has ensued in mass production of clean potato seeds within a short period of time. In support of this, Pruski (2001) revealed that the method is characterized by its flexibility in terms of the rapid multiplication of seedlings. This method has been adopted in several countries like Vietnam where it revolutionized production of potato seeds.…”
Section: Clean Seed Production Technologiesmentioning
confidence: 77%
“…Use of tissue culture technique in seed production has resulted in mass production of potato in a very short period of time. The system is characterized by very flexible and rapid multiplication giving a higher planting propogules (Beukema and Van de Zaag 1990 [4] and Pruski, 2001 [36] , Muthuraj et al, 2016 [26] ). Slowly, micro propagation is replacing conventional propagation of potatoes (Naik and Karihaloo, 2007 [29] , Moeini et al, 2011 [25] ).…”
Section: Hi-tech Methods Of Seed Potato Productionmentioning
confidence: 99%
“…Sīkbumbuļi. Sākotnējās sēklaudzēšanas mērķis ir pēc iespējas ātrāk un ekonomiski izdevīgāk saražot izejmateriālu sēklaudzēšanas saimniecībām un sīkbumbuļu audzēšana ļauj samazināt lauka paaudžu skaitu (Struik, Lommen, 1999;Struik, Wiersema, 1999 (Kotkas, Rosenberg, 1999;Pruski, 2001;Haapala, 2005;Kawakami, Oohori, Tajima, 2015). Tomēr literatūrā atrodami atšķirīgi uzskati par to, vai mātesaugi kā izejmateriāls sēklaudzēšanai būtu jāiegūst katru gadu no jauna (no meristēmām, dzinumu galotnēm vai citādi), vai tomēr var izmantot gēnu bankās un repozitorijos esošo materiālu, kur tas tiek ilgstoši uzglabāts.…”
Section: Sākotnējās Sēklaudzēšanas Metodes Un No Vīrusiem Brīva Izejm...unclassified
“…Kartupeļu mikropavairošanā tiek lietoti arī lielāki in vitro augu audzēšanas trauki, īpaši pēdējā pavairošanas fāzē. Literatūrā minētas 300 mL tilpuma kolbas (Correa et al, 2008), plastmasas konteineri, kuros iepilda 100 mL barotnes (Milinkovic et al, 2012), 5 cm augsti plastmasas trauki, kuru diametrs ir 10 cm un kuros iepildīti 75 mL barotnes , Magenta korporācijā ASV ražotie trauki GA7 (Pruski, 2001) un minēti arī "piemēroti trauki" (Dodds, 1988). Vienā traukā audzēti no 10 līdz pat 25 kartupeļu mikroaugiem.…”
Section: Mikropavairošanas Metodes To Pēcietekme Uz Augu Attīstību Un...unclassified
See 1 more Smart Citation